2012
DOI: 10.3415/vcot-11-03-0043
|View full text |Cite
|
Sign up to set email alerts
|

Patient specific implants for amputation prostheses: Design, manufacture and analysis

Abstract: SummaryObjectives: To design, manufacture and analyze custom implants with functional gradation in macrostructure for attachment of amputation prostheses.Methods: The external shape of the implant was designed by extracting geometrical data of canine cadavers from computed tomography (CT) scans to suit the bone cavity. Three generations of implant designs were developed and were optimized with the help of fit/fill and mechanical performance of implant-cadaver b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…It has been shown that the roughness of the metal surface increases cell apposition . Microroughened and nanosurface superimposed featured implants improved osteogenesis and the inflammatory/immune responses …”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the roughness of the metal surface increases cell apposition . Microroughened and nanosurface superimposed featured implants improved osteogenesis and the inflammatory/immune responses …”
Section: Discussionmentioning
confidence: 99%
“…These techniques are not limited to neoplasia management (13)(14)(15). Potential reported advantages of osseointegrated implants include improved comfort, no delay in load transfer, improved proprioception, and avoidance of stump socket interface problems that are commonly encountered in stump socket prostheses (15,16). However complications including fracture, infection, skin breakdown, and aseptic loosening are all reported.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its insertion in the medullary cavity of long bones, all the disadvantages of a socket prosthesis are avoided. Besides, better proprioception, no delay in load transfer, comfort, and energetic efficiency all have been described (Fitzpatrick et al, 2011;DeVasConCellos et al, 2012;Pitkin, 2013;Phillips et al, 2017). Exo-endoprosthesis complications have been reported, such as device failure, aseptic loss, marsupialization or skin breakdown, avulsion, and infection (Drygas et al, 2008;Fitzpatrick et al, 2011;DeVasConCellos et al, 2012;Golachowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Besides, better proprioception, no delay in load transfer, comfort, and energetic efficiency all have been described (Fitzpatrick et al, 2011;DeVasConCellos et al, 2012;Pitkin, 2013;Phillips et al, 2017). Exo-endoprosthesis complications have been reported, such as device failure, aseptic loss, marsupialization or skin breakdown, avulsion, and infection (Drygas et al, 2008;Fitzpatrick et al, 2011;DeVasConCellos et al, 2012;Golachowski et al, 2019). There are published clinical reports for exo-endoprosthesis for different animal species (Drygas et al, 2008;Fitzpatrick et al, 2011;Golachowski et al, 2019) or experimental models (Hall, 1976;Pitkin, 2013;Farrell et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation